Birth cluster simulations of planetary systems with multiple super-Earths: initial conditions for white dwarf pollution drivers - Stock, Katja; Veras, Dimitri; Cai, Maxwell Xu; Spurzem, Rainer; Zwart, Simon Portegies (Monthly notices of the Royal Astronomical Society, 2022)
Previous investigations have revealed that eccentric super-Earths represent a class of planets that are particularly effective at transporting minor bodies towards white dwarfs and subsequently polluting their atmospheres with observable chemical signatures. However, the lack of discoveries of these planets beyond a few astronomical units from their host stars prompts a better understanding of their orbital architectures from their nascent birth cluster. Here, we perform stellar cluster simulations of three-planet and seven-planet systems containing super-Earths on initially circular, coplanar orbits. We adopt the typical stellar masses of main-sequence progenitors of white dwarfs ($1.5\, M_{\odot }$-$2.5\, M_{\odot }$) as host stars and include 8000 main-sequence stars following a Kroupa initial mass function in our clusters. Our results reveal that about 30 per cent of the simulated planets generate eccentricities of at least 0.1 by the time of cluster dissolution, which would aid white dwarf pollution. We provide our output parameters to the community for potential use as initial conditions for subsequent evolution simulations.
Gesehen am 22.04.2022